Mechanical Ventricular Assistance as Destination Therapy for End-Stage Heart Failure: Has it Become a First Line Therapy? - Bonacchi, Massimo; Harmelin, Guy; Bugetti, Marco; Sani, Guido (Frontiers in Surgery, 2015)
Patients with end-stage heart failure have poor quality of life and prognosis.Therapeutic options are scarce and not available for all:only few patients can be transplanted and several medical and surgical strategies have shown limited ability to influence prognosis and quality of life. In the past years, technological progress has realized devices capable of providing appropriate hemodynamic stabilization and recovery of secondary organ failure. In the recent years,these devices are assessed and discussed as definitive treatment for patients who do not qualify for transplantation or/and instead to transplantation (“destination therapy”). This indication is increasingly considered following the results of newest clinical study reporting long-term survival without device correlated adverse events using last generation devices, and acceptable quality of life. The current knowledge about Destination Therapy and some original data from the DAVID Study (an Italian multicenter prospective study designed to evaluate the patient’s survival rate and quality of life of patients implanted with these new devices as long-term support or destination therapy) are summarized.